Use of encapsulated L-lysine-HCl and DL-methionine improves postprandial amino acid balance in laying hens. (21st September 2020) - Sun, Mingfa; Zhao, Jingpeng; Wang, Xiaojuan; Jiao, Hongchao; Lin, Hai
Abstract: The supplementation of dietary limiting amino acids (AA ) with crystalline AA makes the use of low-protein diets an option in poultry production. The differing absorption rates of crystalline and protein-bound AA may lead to temporally imbalanced AA in the postabsorptive period. In this study, two experiments were conducted to evaluate the effect of encapsulated L-lysine-HCl (L-Lys-HCl ) and DL-methionine (DL-Met ) on the laying performance of hens. In exp. 1, a total of 135 forty-seven-wk-old Hy-Line Brown hens were subjected to three dietary treatments for 8 wk: basal diet supplemented with 0.14% L-Lys-HCl and 0.17% DL-Met to satisfy the NRC (1994) total Lys and Met recommendation (control) and basal diet supplemented with encapsulated L-Lys-HCl and DL-Met at the levels of 60% (60CLM, 0.084% L-Lys-HCl and 0.102% DL-Met) or 80% of control (80CLM, 0.112% L-Lys-HCl and 0.136% DL-Met), respectively. In exp. 2, 24 fifty-five-wk-old Hy-Line Brown hens were individually reared in cages and subjected to the same treatments as in exp. 1. The plasma concentrations of free AA and nitrogen metabolites were measured 2, 4, and 6 h after fed. The results showed that dietary AA treatment had no significant influence on body weight (BW ), feed intake, laying rate, egg weight, egg mass, or feed efficiency. The expression levels of AA transporters CAT-1, y + LAT1, b 0, + AT, B 0 AT, rBAT, EAAT3, and PepT1 in the duodenum, jejunum, and ileum were not influenced ( P > 0.05) by dietary treatment. There was an interaction of dietary AA treatment and time ( P < 0.05) and the 80CLM hens exhibited higher concentrations of Lys ( P < 0.05) than the controls at 2-h time point. In contrast, plasma Met concentration was not influenced ( P > 0.05), while Cys was reduced in the 60CLM hens at every time point. The 80CLM hens had higher taurine concentrations than those receiving the control diet at every postprandial time point. In conclusion, these findings demonstrate that by using encapsulated form, the supplemental levels of synthetic L-Lys-HCl and DL-Met can be effectively reduced by approximately 20% with no negative effect on laying performance. The result suggests that encapsulated Lys and Met may ameliorate the postabsorptive AA balance and contribute to the reduced dietary AA supplemental levels.